Comparison of student attitudes towards natural sciences - Maison Maison; Haryanto Haryanto; Margaret Dwi Wiwik Ernawati; Yulia Ningsih; Nurdatul Jannah; Tari Okta Puspitasari; Dodi Setiawan Putra (Institute of Advanced Engineering and Science, 2020)
The attitude of students during the learning process is essential to be known by an educator to understand how to deal with students in the class. This study aims to determine how students 'attitudes towards science subjects and this study also aim to determine whether there is a comparison of students' attitudes towards natural science subjects in junior high schools in Indonesia. This research was conducted at some state junior high schools in Jambi. Specifically, the research sites were Junior High School 5, Junior High School 6, and Junior High School 26 in Jambi. The research design used in this study was a quantitative approach with survey methods. The research instrument was a science attitude questionnaire. Data were analyzed using descriptive statistics and inferential statistics. The results showed that students' attitudes toward science subjects based on indicators of adoption of scientific attitudes, fun in learning science, and interest in increasing the time to study science were in good categories and also there are significant differences of students’ attitude towards science subjects in the three schools with a comparison value of 0.042 < 0.05.